menu
bartleby
search
close search
Hit Return to see all results

Using the Product Rule In Exercises 5-10,use the Product Rule to find the derivative of thefunction.6. y (3x - 4)(x3 +5)8. g(s) s(s2 + 8)10. g(x)= x sin x2x- 3)(1 - 5x)5. g(४) =7. ht)- P)9. f(x)= x cosxUsing the Quotient Rule In Exercises 11-16,use the Quotient Rule to find the derivative of thefunction.3r2 112. g(t)2t +511. f(x)x5x- 514. f(x) 2x+ 113. hx)3 115. glx)Sinx15. g(४) =x2COs t16. f(t)t3sFinding and Evaluating a Derivative InExercises 17-22, find f'(x) and f'(c).FunctionValue of c17. f(x) (3 4x) (3x2 2x-5)18. f(x) = (22- 3x) (9x + 4)c 0wc -119. f(x)2-4x - 3sec = 120. f(x)4c 3x + 4

Question

13

Using the Product Rule In Exercises 5-10,
use the Product Rule to find the derivative of the
function.
6. y (3x - 4)(x3 +5)
8. g(s) s(s2 + 8)
10. g(x)= x sin x
2x- 3)(1 - 5x)
5. g(४) =
7. ht)
- P)
9. f(x)= x cosx
Using the Quotient Rule In Exercises 11-16,
use the Quotient Rule to find the derivative of the
function.
3r2 1
12. g(t)2t +5
11. f(x)x5
x- 5
14. f(x) 2x+ 1
13. hx)3 1
15. glx)Sinx
15. g(४) =
x2
COs t
16. f(t)
t3s
Finding and Evaluating a Derivative In
Exercises 17-22, find f'(x) and f'(c).
Function
Value of c
17. f(x) (3 4x) (3x2 2x-5)
18. f(x) = (22- 3x) (9x + 4)
c 0
w
c -1
19. f(x)2-4
x - 3
se
c = 1
20. f(x)
4
c 3
x + 4
help_outline

Image Transcriptionclose

Using the Product Rule In Exercises 5-10, use the Product Rule to find the derivative of the function. 6. y (3x - 4)(x3 +5) 8. g(s) s(s2 + 8) 10. g(x)= x sin x 2x- 3)(1 - 5x) 5. g(४) = 7. ht) - P) 9. f(x)= x cosx Using the Quotient Rule In Exercises 11-16, use the Quotient Rule to find the derivative of the function. 3r2 1 12. g(t)2t +5 11. f(x)x5 x- 5 14. f(x) 2x+ 1 13. hx)3 1 15. glx)Sinx 15. g(४) = x2 COs t 16. f(t) t3s Finding and Evaluating a Derivative In Exercises 17-22, find f'(x) and f'(c). Function Value of c 17. f(x) (3 4x) (3x2 2x-5) 18. f(x) = (22- 3x) (9x + 4) c 0 w c -1 19. f(x)2-4 x - 3 se c = 1 20. f(x) 4 c 3 x + 4

fullscreen
check_circleAnswer
Step 1

Note: We will answer the question (5) since the exact one wasn’t specified. And it has the multiple questions from (5-10). Please submit a new question specifying the one you’d like to answered.

Step 2

The given function is

g(x)(2x-3)1-5x)
help_outline

Image Transcriptionclose

g(x)(2x-3)1-5x)

fullscreen
Step 3

And it is required to find the d...

g(x) = (2.x-3)(1-5x) using the product rule of differentiation
help_outline

Image Transcriptionclose

g(x) = (2.x-3)(1-5x) using the product rule of differentiation

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Our solutions are written by experts, many with advanced degrees, and available 24/7

See Solution
Tagged in

Math

Calculus

Derivative

Sorry about that. What wasn’t helpful?